Costs of reusable and disposable aprons in a public teaching hospital - Paloma de Souza Cavalcante Pissinati; Maria do Carmo Lourenço Haddad; Mariana Ângela Rossaneis; Roseli Broggi Gil; Renata Aparecida Belei (SciELO, 2014)
Objective To analyze the direct cost of reusable and disposable aprons in a public teaching hospital. Method Cross-sectional study of quantitative approach, focusing on the direct cost of reusable and disposable aprons at a teaching hospital in northern Paraná. The study population consisted of secondary data collected in reports of the cost of services, laundry, materials and supplies division of the institution for the year 2012 Results We identified a lower average cost of using disposable apron when compared to the reusable apron. The direct cost of reusable apron was R$ 3.06, and the steps of preparation and washing were mainly responsible for the high cost, and disposable apron cost was R$ 0.94. Conclusion The results presented are important for hospital managers properly allocate resources and manage costs in hospitals .